A meta-analysis of previous fracture and subsequent fracture risk. - Kanis, J; Johnell, O; De Laet, C; Johansson, H; Oden, A; Delmas, P; Eisman, J; Fujiwara, S; Garnero, P; Kroger, H; McCloskey, E; Mellstrom, D; et al. (2004)
Previous fracture is a well-documented risk factor for future fracture. The aim of this study was to quantify this risk on an international basis and to explore the relationship of this risk with age, sex, and bone mineral density (BMD). We studied 15259 men and 44902 women from 11 cohorts comprising EVOS/EPOS, OFELY, CaMos, Rochester, Sheffield, Rotterdam, Kuopio, DOES, Hiroshima, and two cohorts from Gothenburg. Cohorts were followed for a total of 250000 person-years. The effect of a prior history of fracture on the risk of any fracture, any osteoporotic fracture, and hip fracture alone was examined using a Poisson model for each sex from each cohort. Covariates examined were age, sex, and BMD. The results of the different studies were merged by using the weighted beta-coefficients. A previous fracture history was associated with a significantly increased risk of any fracture compared with individuals without a prior fracture (RR = 1.86; 95% CI = 1.75-1.98). The risk ratio was similar for the outcome of osteoporotic fracture or for hip fracture. There was no significant difference in risk ratio between men and women. Risk ratio (RR) was marginally downward adjusted when account was taken of BMD. Low BMD explained a minority of the risk for any fracture (8%) and for hip fracture (22%). The risk ratio was stable with age except in the case of hip fracture outcome where the risk ratio decreased significantly with age. We conclude that previous history of fracture confers an increased risk of fracture of substantial importance beyond that explained by measurement of BMD. Its validation on an international basis permits the use of this risk factor in case finding strategies.